(untitled) (Економіка і регіон/ Economics and region, 2022)
The article defines the goals, tasks, tools and expected results of the implementation of the concept of modernization of the vocational education system as a lever for stimulation of the socio-economic development of Ukraine in the conditions of today’s competitive challenges of global and macro-regional scale. The set of influences and functions of the vocational education system in the economic and non-economic spheres of life (first of all, resource-reproductive, standard and worldview-forming, innovation-producing and -transferring, social-stabilizing) embodies a number of significant factors of competitiveness for countries, national producers, certain communities (territorial, functional), social groups and individuals in the main areas of competition (in the domestic and foreign markets of goods, services, labor; in the framework of cross-border, nationwide, regional mechanisms of access to free services provided by the state and regional order, as well as to the respective levels of socio-economic development funds). Civilizing tendencies and economic practices of the developed countries stimulate the national civil society to realize a number of demands to provide the average individual with decent opportunities to meet the needs for quality educational services, professional acquisition, confirmation and improvement of qualifications regardless of the place of residence, equalization of appropriate starting conditions in local communities and regions, as well as to improve the efficiency of public and state control over the corresponding legislative and social-labor guarantees’ implementation.